Clinical outcomes in children and adolescents initiating antiretroviral therapy in decentralized healthcare settings in Zimbabwe. Issue 1 (1st September 2017) - McHugh, Grace; Simms, Victoria; Dauya, Ethel; Bandason, Tsitsi; Chonzi, Prosper; Metaxa, Dafni; Munyati, Shungu; Nathoo, Kusum; Mujuru, Hilda; Kranzer, Katharina; Ferrand, Rashida A.
Abstract: Introduction : Decentralized HIV care for adults does not appear to compromise clinical outcomes. HIV care for children poses additional clinical and social complexities. We conducted a prospective cohort study to investigate clinical outcomes in children aged 6–15 years who registered for HIV care at seven primary healthcare clinics (PHCs) in Harare, Zimbabwe. Methods : Participants were recruited between January 2013 and December 2014 and followed for 18 months. Rates of and reasons for mortality, hospitalization and unscheduled PHC attendances were ascertained. Cox proportional modelling was used to determine the hazard of death, unscheduled attendances and hospitalization. Results : We recruited 385 participants, median age 11 years (IQR: 9–13) and 52% were female. The median CD4 count was 375 cells/mm 3 (IQR: 215–599) and 77% commenced ART over the study period, with 64% of those who had viral load measured achieving an HIV viral load <400 copies/ml. At 18 months, 4% of those who started ART vs. 24% of those who remained ART‐naïve were lost‐to‐follow‐up ( p < 0.001). Hospitalization and mortality rates were low (8.14/100 person‐years (pyrs) and 2.86/100 pyrs, respectively). There was a high rate of unscheduled PHC attendances (34.94/100 pyrs), but only 7% resulted in hospitalization. Respiratory disease was the major cause of hospitalization, unscheduled attendances and death. CD4 count <350cells/mm 3 was a risk factor for hospitalization (aHR 3.6 (95%CI 1.6–8.2)). Conclusions : Despite only 64% of participants achieving virological suppression, clinical outcomes were good and high rates of retention in care were observed. This demonstrates that in an era moving towards differentiated care in addition to implementation of universal treatment, decentralized HIV care for children is achievable. Interventions to improve adherence in this age‐group are urgently needed.